All‐Aqueous Emulsions: Generation of High‐Order All‐Aqueous Emulsion Drops by Osmosis‐Driven Phase Separation (Small 39/2018). Issue 39 (26th September 2018) - Chao, Youchuang; Mak, Sze Yi; Rahman, Shakurur; Zhu, Shipei; Shum, Ho Cheung
Abstract : In article number1802107, Ho Cheung Shum and co‐workers demonstrate an approach to produce high‐order, up to quadruple, all‐aqueous emulsion drops, which are initiated by osmosis‐induced phase separation from non‐equilibrium aqueous two‐phase systems on a glass‐based microfluidic platform. The complexity of the generated all‐aqueous emulsion drops is well predicted in a phase diagram, providing a strategy to fabricate all‐aqueous emulsions with a tunable high‐order structure.